Clustering student satisfaction using SERVQUAL and K-means methods - Gunawan, Akbar; Wahyuni, Nuraida; Wibowo, Habibi Urfa; Fachrur, Aditya Rahadian; Khatili, Putiri Buana; Barleany, Dhena Ria (Jurnal Teknika, 2024)
Student satisfaction is a critical indicator of higher education service quality. Higher education institutions must maintain student satisfaction to ensure service quality. This study measures and analyzes student satisfaction at higher education institutions using the SERVQUAL model to inform service improvement strategies. A survey assessed five key service dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Gap analysis and non-hierarchical K-means clustering identified six student groups with varying satisfaction levels. Cluster 1, with an average gap score of -3.00 and a Customer Satisfaction Index (CSI) of 65.68%, was categorized as 'less satisfied' and prioritized for improvement. Importance Performance Analysis (IPA) identified critical service attributes. Improvement strategies; developed using the 5W+1H framework (Who, What, Where, When, Why, and How); emphasize enhanced communication, faster service delivery, strengthened employee competencies, and a student-centered organizational culture. These findings provide a robust foundation for strategic decision-making to enhance service quality in higher education institutions.